Интенсификация вертикального турбулентного обмена в районах сопряжения шельфа и континентального склона в Черном море - Иванов, В.А.; Самодуров, А.С.; Чухарев, А.М.; Носова, А.В. (Видавничий дім "Академперіодика" НАН України, 2008)
The dependence of the vertical turbulent exchange intensity on the local stratification in stratified layers of the Black Sea near the interface between the shelf and the continental slope is estimated by the data of field measurements. The field experiments were performed within the framework of the international projects GEF/BSERP (May, 2004) and “Black Sea - 2004”(July, 2004) and also the national projects (May, 2007). Information is got with the use of the probing system “Sigma-1” [1]. As a data processing tool, the method [2, 3] of estimation of the vertical turbulent diffusion coefficient depending on external conditions is used. The mean values of the coefficient of turbulent exchange in all explored regions proved to be substantially greater (approximately by one order of magnitude) as compared to that under conditions of the open sea for the identical local stratification. This can be related to a peculiarity of the bottom topography influencing the dynamics of quasiinertial internal waves which serve here as a basic reason of the small-scale mixing and vertical diffusion.